Promoting the autonomy of rural older adults in active aging - Celmira Lange; Ivonete Teresinha Schülter Buss Heidemann; Denise Somavila Przylynski Castro; Andressa Hoffmann Pinto; Carla Weber Peters; Michelle Kuntz Durand
ABSTRACT Objective: to understand how the rural older adults promote their autonomy in active aging. Method: qualitative research through the Paulo Freire's research itinerary, consisting of three steps: area of research; encoding and decoding; and critical unveiling. Seventeen older adults living in the rural area of a municipality in Southern Brazil participated in the research. Six culture circles were conducted from July to December 2016. Results: the investigation revealed two generating themes: joint pain and participation in groups. The understanding of autonomy promotion for the active aging of older adults is focused on the physical capacity and independence of activities of daily living. Final considerations: the culture circles have promoted reflection moments for the participants, especially about the advantages and difficulties related to the practice of autonomy in the exercise of citizenship for active aging in the rural area.